CRITICAL THINKING: A STUDY OF IRANIAN EFL READING COMPREHENSION PERFORMANCE - Mansour Fahim; Hamed Barjesteh (University of Muhammadiyah Purwokerto, 2011)
The development of critical thinking (CT) skills has become a key goal for educators in first and second language contexts. There is evidence that the use of such activities has still not become widespread in a number of ELT situations. One reason for this may be lack of awareness about how levels of thinking can be conceptualized in ELT activities. It is argued that learners studying English for general purposes (EGP) have a particular need for activities which are not only linguistically manageable but also cognitively challenging. This paper reports on a program designed by the author at a university in Iran, which used taxonomy of CT skills drawn up by Facione (1990) to probe the effect of critical thinking strategies training on reading comprehension of Iranian EFL students. In so doing, 240 male and female Iranian EFL students were selected and screened into two proficiency levels based on the TOEFL tests. Each proficiency group was divided into critical and non-critical group. The results suggested CT skills significantly affected EFL learners’ reading comprehension performance. However, the effect of critical thinking strategy training didn’t vary across different language proficiency levels. Overall, the findings provide empirical support for the facilitative effect of critical thinking strategy training on reading comprehension performance of EFL learners.